Detection and characterizacion of Colombian wetlands using Alos Palsar and MODIS imagery - L.M. Estupinan-Suarez; C. Florez-Ayala; M.J. Quinones; A.M. Pacheco; A.C. Santos (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
Wetlands regulate the flow of water and play a key role in risk management of extreme flooding and drought. In Colombia, wetland conservation has been a priority for the government. However, there is an information gap neither an inventory nor a national baseline map exists. In this paper, we present a method that combines a wetlands thematic map with remote sensing derived data, and hydrometeorological stations data in order to characterize the Colombian wetlands. Following the adopted definition of wetlands, available spatial data on land forms, soils and vegetation was integrated in order to characterize spatially the occurrence of wetlands. This data was then complemented with remote sensing derived data from active and passive sensors. A flood frequency map derived from dense time series analysis of the ALOS PALSAR FBD /FBS data (2007-2010) at 50m resolution was used to analyse the recurrence of flooding. In this map, flooding under the canopy and open water classes could be mapped due to the capabilities of the L-band radar. In addition, MODIS NDVI profiles (2007-2012) were used to characterize temporally water mirrors and vegetation, founding different patterns at basin levels. Moreover, the Colombian main basins were analysed and typified based on hydroperiods, highlighting different hydrological regimes within each basin. The combination of thematic maps, SAR data, optical imagery and hydrological data provided information on the spatial and temporal dynamics of wetlands at regional scales. Our results provide the first validated baseline wetland map for Colombia, this way providing valuable information for ecosystem management.